The comparison of the chronic-phase vascular healing between bioabsorbable and durable polymer drug eluting stent by using optical coherence tomography. (25th November 2020) - Yamakami, Y; Kimura, S; Hara, K; Ohmori, M; Tateishi, R; Kaneda, T; Shimada, H; Manno, T; Isshiki, A; Shimizu, M; Fujii, H; Suzuki, M; et al.
Abstract: Background: Bioabsorbable polymer drug eluting stents (BP-DESs) were designed to reduce a vascular inflammatory reaction compared to durable polymer drug eluting stents (DP-DESs). However, few studies have compared vascular responses to BP-DESs and DP-DESs. Methods: We enrolled 88 consecutive patients with single culprit coronary artery lesions (31 lesions with acute coronary syndrome) undergoing a single stent-implantation. BP-DESs and DP-DESs were implanted in 50 (57%) and 38 patients (43%), respectively. All lesions underwent optical coherence tomography examination at chronic phase and intrastent OCT findings at the follow-up were evaluated in every 1-mm cross-sections (CSs). Results: A total of 1887 CSs (BP-DES: 1096, DP-DES: 791) were analyzed. The median period of follow-up OCT was 293 (250–374) days. There were no differences in the patient, lesion, and initial clinical presentation of acute coronary syndrome (ACS). BP-DESs had significantly higher percent neointimal hyperplasia area, defined as neointimal hyperplasia area divided by stent area x 100 (18.4±9.0% vs. 16.1±9.9%, p<0.001), fewer malapposed struts (1.7% vs. 3.9%, p=0.005), fewer uncovered struts (3.6% vs. 5.8%, p=0.02) but higher frequency of superficial low intensity neointima (LIN) (7.7% vs. 3.4%, p<0.001). Multivariate logistic analysis showed that BP-DES (OR: 2.5, 95% CI: 1.49–4.08, p<0.001) and the initial clinical presentation of ACS (OR: 2.31, 95% CI: 1.47–3.62, p<0.001) are independent predictive factors for LIN. Conclusion: BP-DESs showed homogenous neointimal growth and complete stent coverage quantitatively. Meanwhile, the significant relationships of BP-DES with LIN may suggest that the neointimal quality remains immature in BP-DESs in this period. Funding Acknowledgement: Type of funding source: None